Factors associated with use of long lasting insecticidal net in Kailali District, Nepal - Thakurathi, Bhuwan; Sangroula, Raj Kumar; Joshi, Om Prakash; Giri, Raksha; Gurung, Suman Chandra; Adhikari, Nilam; Thakurathi, Mohan (International Journal Of Community Medicine And Public Health, 2020)
Background: Malaria is the protozoan disease caused by the parasite of genus plasmodium. As per the World Health Organization Global Malaria Program, the primary intervention for effective malaria control is distribution of insecticide-treated nets, more specifically long-lasting insecticidal net, to achieve full coverage of populations at risk of malaria. The aim of the study was to identify associated factors with use of long-lasting insecticidal net in Kailali district. Methods: A community based quantitative cross-sectional study was carried out in 5 village development committees of Kailali district. Altogether 450 households which were determined based on probability proportional to household size. Analysis of association was made by bivariate logistic regression and multivariate logistic regression. Ethical approval was taken from Institutional Review Board, Institute of Medicine and written informed consent from each participant. Results: The study showed the proportion of use of long-lasting insecticidal net was 60% and net retention rate was about 96%. About 53% of households had net density of less than 0.5. Almost one-third of respondents had good knowledge about malaria. There were bad practices regarding to handling of nets. The study found strong significant association between long lasting insecticidal net use and factors such as wealth status, education, net density and knowledge about malaria. Conclusions: There were some bad practices in regards to handling nets. It needs to be focused on net utilization behaviours change activities. Further extensive study particularly qualitative one on behaviours related to use of bed nets should be carried out.